Inovasi Kepala Madrasah dalam Penyiapan Pembelajaran Daring di MTS Negeri 4 Sragen - Efendi, Abdul Haritsah (Nur Science Institute, 2021)
The objectives of this study were 1) to describe the leadership of the principal of MTs Negeri 4 Sragen, 2) to describe the online learning at MTs Negeri 4 Sragen, 3) to describe the role of principal leadership in online learning at MTs Negeri 4 Sragen. This research uses qualitative research. This research includes ethnographic research that describes and interprets socio-cultural groups. Sources of data in this study were the principal, the vice principal of the curriculum section, the deputy principal of the school for facilities and infrastructure, and teachers. Data collection techniques were used observation, interviews, and documentation. Descriptive analysis was used in thus study.. The data validity used triangulation. The final results of the study conclude that 1) the leadership of the principal of MTs Negeri 4 Sragen is a type of democratic leadership in which the decision-making process is carried out collectively by collegial, meaning that the principal of MTs Negeri 4 Sragen is a leader who also trusts his staff because the school's small activities cannot be reached by the principal. , 2) online learning by Dramaga 1 Public High School teachers is that students can study anytime and anywhere, without being limited by time and space. Students can also interact with the teacher at the same time, such as using video calls or live chat. Online learning can be provided electronically using forums or messages or other platforms, 3) the role of the principal as a leader in online learning at MTs Negeri 4 Sragen is to form a special team, namely the IT MTS NEGERI 4 SRAGEN team, where this team is in charge of guiding teachers in order to understand technology. The results of the data that have been obtained show that the role of the principal at MTs Negeri 4 Sragen has played the role of educator, manager, administrator, supervision, innovator, motivator and leader in directing teachers to online learning systems or distance learning during the Covid-19 pandemic.